(untitled) (Journal of Preventive and Social Medicine, 2022)
Background: Tobacco use has become one of the major causes of premature deaths in developing countries including Bangladesh. Incidence of tobacco consumption among the women in developing country is increased day by day. The objective of this study was to assess the knowledge of slum dwelling adult women regarding harms of tobacco use. Materials & Methods: This descriptive type of cross-sectional study was conducted in selected urban slums of Dhaka North City Corporation from 1st January 2021 to 31st December 2021. Total 300 slum dwelling adult women was selected by convenience sampling technique. Data were collected through face to face interview using a pre-tested semi structured questionnaire. Results: In the study, the mean age of the respondents was 32 (± 6.96) years where maximum (44.3%) within the age group of 20-29 years. Majorities (97%) of the respondents were muslim and 93.7% were married. Among them 29% women were completed primary education. Most (59.3%) of the respondents were home maker and majority (96.0%) of them were came from nuclear family. The study showed that most (56%) of the respondents consumed smokeless tobacco (Jarda, Sada pata, Gul) and only 1.7% respondents consumed smoking tobacco (bidi). Majority of the women knew that tobacco use can cause different types of cancer but many of them did not know that tobacco use had detrimental effects on reproductive health of women. Television (44.3%) was the main source of the information about harms of tobacco use. The mean knowledge score of the respondents was 7.8 (±2.4). Association between most of the socio-demographic variables and the respondent’s knowledge score regarding harms of tobacco use was found statistically significant (p< 0.05). Conclusion: This study revealed that the educational levels of most of the slum women were low and they had the lowest mean knowledge score regarding harmful effects of tobacco use. Health educational programs and awareness campaigns should be conducted among slum dwelling women of urban community to increase their knowledge on harmful effects of tobacco use. JOPSOM 2021; 40(2): 58-64